The Phenomenon of Arabic Phonological Assimilation at the Beginner Level in Islamic Boarding Schools - Umi Badriatus Sholihah; Maskud; Syamsul Anam (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
This study aims to describe the phenomenon of Arabic phonological assimilation among beginner students in Islamic boarding schools, with a particular focus on the application of idghām rules. The research is motivated by the observation that many novice learners struggle to connect written Arabic texts with accurate pronunciation, which affects their reading fluency and comprehension. The study employed a qualitative case study design using classroom observations, semi-structured interviews, and documentation as data collection techniques. The data were analyzed descriptively to identify phonological errors and the underlying factors contributing to assimilation difficulties. The findings reveal that beginner learners encounter significant challenges in applying the rules of idghām, mainly due to limited phonological awareness, the absence of explicit phonological instruction, and interference from their native language. However, the results also indicate that systematic guidance and repeated practice gradually improve students’ pronunciation accuracy. The implications of these findings highlight the importance of developing explicit, contextual, and technology-based phonological instruction that addresses the specific needs of beginner learners in Islamic boarding schools. Furthermore, the study opens avenues for future research to compare phonological acquisition in pesantren and formal schools, evaluate the effectiveness of digital media in supporting phonological awareness, and conduct longitudinal studies to trace the development of assimilation competence over time.